THE EFFECTS OF DIFFERENT ENGINE MATERIAL PROPERTIES ON THE PERFORMANCE OF A DIESEL ENGINE AT MAXIMUM COMBUSTION TEMPERATURES - Palaci, Yuksel; Gonca, Guven (VINCA INST NUCLEAR SCI, 2020)
In this study, the influences of various engine materials such as palladium, titanium, thorium, zirconium, vanadium, alumina, aluminum bronze, copper, iron (gray cast), manganese, nickel, cobalt, and carbon steel on the effective efficiency and effective power with respect to the variation of equivalence ratio at the maximum combustion temperatures. In-cylinder gas temperatures have been determined with respect to the melting temperatures and the performance values have been calculated with respect to the variation of the gas temperatures. The results indicated that alumina provides the maximum performance values as aluminum bronze gives the minimum performance values due to the combustion temperatures. Furthermore, the equivalence ratios which give the maximum performance characteristics have been parametrically described. The obtained results can be assessed by engine designers and manufacturers to choose suitable engine material.
Keywords: engine material; performance; combustion temperatures; Diesel engine; equivalence ratio; IRREVERSIBLE MILLER CYCLE; HEAT-TRANSFER; STEAM INJECTION; DUAL CYCLE; PARAMETERS; RATIO; MAPS; Thermodynamics